Kerajaan Islam Andalus Sebagai Model Keharmonian Hubungan Etnik: The Muslim Government of Al-Andalus as a Model of Harmonious Ethnic Relations - Nik Abdullah, Nik Kamaliah (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
The community is now faced with various problems in particular in the context of public life of different ethnic groups. This article highlights the Islamic Government as a model of ancient Andalus government capable of building harmony within society different religion, nationality and ancestry. This government experience featuring Islamic approach in facing the community at the time when it involves political economic and social have made European world torch as Andalus.